A family 11 carbohydrate binding module (CBM) improves the efficacy of a recombinant cellulase used to supplement barley-based diets for broilers at lower dosage rates - Lordelo, M.M. (2009)
1. Exogenous microbial -1,3-1,4-glucanases and hemicellulases contribute to improving the nutritive value of cereals rich in soluble non-starch polysaccharides for poultry. 2. In general, plant cell wall hydrolases display a modular structure comprising a catalytic module linked to one or more non-catalytic carbohydrate-binding modules (CBMs). Based on primary structure similarity, CBMs have been classified in 50 different families. CBMs anchor cellulases and hemicellulases into their target substrates, therefore eliciting efficient hydrolysis of recalcitrant polysaccharides. 3. A study was undertaken to investigate the effects of a family 11 -glucan-binding domain in the function of recombinant derivatives of cellulase CtLic26A-Cel5E of Clostridium thermocellum that were used to supplement a barley-based diet at lower dosage rates. 4. The results showed that birds fed on diets supplemented with the recombinant CtLic26A-Cel5E modular derivative containing the family 11 CBM or the commercial enzyme mixture RovabioTM Excel AP tended to display improved performance when compared to birds fed diets not supplemented with exogenous enzymes. 5. It is suggested that at lower than previously reported enzyme dosage (10 U/kg vs 30 U/kg of basal diet), the -glucan-binding domain also elicits the function of the recombinant CtLic26A-Cel5E derivatives. 6. Finally, the data suggest that exogenous enzymes added to barley-based diets act primarily in the proximal section of the gastrointestinal tract.